2009
DOI: 10.1016/j.ijsu.2009.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic occult cysto-biliary communication without bile into cavity of the liver hydatid cyst: A pitfall in conservative surgery

Abstract: The predictors demonstrated in this study should allow the likelihood of occult insidious cysto-biliary communication to be determined and, thus, indicate the need for additional procedures during operations to prevent the complications of biliary leakage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
49
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 23 publications
4
49
0
Order By: Relevance
“…In another study including 183 cases with occult and asymptomatic cysts, Unalp el al. (10) reported that a cyst diameter of more than 10 cm predicted post-operative bile leak. In the current study, we also found that the cyst diameter was a significant predictor for the presence of CBF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study including 183 cases with occult and asymptomatic cysts, Unalp el al. (10) reported that a cyst diameter of more than 10 cm predicted post-operative bile leak. In the current study, we also found that the cyst diameter was a significant predictor for the presence of CBF.…”
Section: Discussionmentioning
confidence: 99%
“…cyst cases) (5,(8)(9)(10)) is usually asymptomatic and may be diagnosed intra-operatively (bile within the cyst) or post-operatively by an external biliary fistula through a drain or wound. Frank or major fistula is a wide communication between the cyst and the biliary system that allows the contents of the cyst to drain into the biliary system causing obstructive jaundice, cholangitis, secondary infection of the cyst, or even anaphylaxis (11).…”
Section: Introductionmentioning
confidence: 99%
“…Although this method seems to be the most complete treatment for hydatid disease, it is indicated when cysts have destroyed an entire lobe or segment, thus compressing the healthy parenchyma interrupting the bile ducts, or there is the need to resect draining zones of fistulised bile ducts. In such cases left or right hepatectomy or segmentectomy can be performed [12,[23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Liver hydatidosis is a zoonotic disease which is caused by the larvae of the genus Echinococcus and is endemic to certain areas of the planet [1,2,3,4,5,6,7,8,9,10,11,12,13]. Among the complications that liver hydatid cysts (LHC) may cause, the most common (and the most serious) is communication between the LHC and the bile duct [3,4,5,6,7,8,9,10,11,12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Among the complications that liver hydatid cysts (LHC) may cause, the most common (and the most serious) is communication between the LHC and the bile duct [3,4,5,6,7,8,9,10,11,12,13,14]. Cystobiliary communication (CBC) may occur anywhere in the bile duct.…”
Section: Introductionmentioning
confidence: 99%